18F-FDG PET/CT Imaging of Epididymal Smooth Muscle Mass Mimicking Recurrent Lymphoma. (April 2017) - Takeuchi, Shogo; Inubushi, Masayuki; Nagai, Kiyohisa; Sone, Teruki
Abstract : Abstract: An 84-year-old man with a history of diffuse large B-cell lymphoma in remission who had completed chemotherapy 3 years previously was referred for imaging evaluation of disease recurrence. Abnormal accumulation in the left scrotum was demonstrated on 18 F-FDG PET/CT. Subsequent ultrasonography showed a nodular mass lesion in the left epididymis. He then underwent left orchiectomy. Histopathological examination of the mass diagnosed smooth muscle hyperplasia/hamartoma of the left epididymis. Epididymal smooth muscle hyperplasia/hamartoma should be included as a differential diagnosis for malignant scrotal tumor.